The Relationship Between Low Birth Weight Neonates And Asphyxia Neonatorum at Ariï¬n Achmad Hospital: Hubungan Berat Badan LahirRendah (BBLR) DenganAsfiksiaNeonatorumDiRSUDArifin Achmad - juli selvi yanti (STIKes Hang Tuah Pekanbaru, 2017)
ABSTRACT Asphyxia is breathing difficulty that occurs in newborns. Low birth weight (LBW) neonates often suffer from asphyxia, this are due to surfactant deficiency, incomplete lung growth, weak respiratory muscles, and easily bent ribs, therefore it can not supply oxygen enough of the placenta. Data from Arifin Achmad Hospital showed that the number of neonatal asphyxia includes 15 largest disease as the cause of infant mortality. In 2014 from January to September there were 36 cases of asphyxia of 955 newborns (3.76%). The purpose of this study was to determine the relationship between LBW and asphyxia neonatorum at Arifin Achmad Hospital Riau Province in 2014. This research method used quantitative analytical research and the design was case control. This research was conducted at Arifin Achmad Hospital Riau Province on March 3 until May 3 2015. The population in this study was all newborn babies who born at Arifin Achmad Hospital and samples were 72 respondents which consisted of 36 cases and 36 control. The sampling technique was simple random sampling. Data collection used secondary data by using a checklist sheet, data was processed by computer and data analysis used univariate and bivariate. The results from the chi square test showed that there was a relationship between LBW and asphyxia indicated by p value = 0.002 <0.05. It is expected that health professionals can provide information about the factors related to asphyxia as low birth weight, risk factor of maternal nutritional status to the mother and fetus. In addition, to health workers are also expected to provide information to pregnant women about how to prevent LBW and asphyxia by providing brochures, leaflets and others.